IMPACT OF SAFETY COMMUNICATION ON SAFETY COMMITMENT IN AN OIL AND GAS COMPANY: LMX AS THE MODERATING FACTOR - ABDUL RASHID, RAFIDAH (2016)
As in many countries, issues on occupational safety and health havebeen emphasized in high hazard work environments including in the oil and gas industry due to the frequent number of accidents and injuries that have occurred at the workplace. Communication pertaining to safety plays a crucial role in disseminating and sharing information on safety related issues in organizations with highly hazardous work environment. However, safety communication is still lacking in the occupational safety studies specifically on impact studies on the safety outcome such as safety commitment. The implementation of safely activities in high hazard organization becomes a challenge due to the lack quality interactions amongst the management and employees and lack of commitment from the employees can increase the frequency of accidents and incidents at the workplace.